Molecular structure evolution of Type I kerogen during pyrolysis: Case study from the Songliao Basin, NE China. (December 2021) - Cao, Huairen; Lei, Yan; Wang, Xiaoyu; Zou, Yan-Rong; Peng, Ping'an
Abstract: To characterize molecular structure evolution of Type I kerogen, we performed gold tube pyrolysis experiments on a Cretaceous Qingshankou lacustrine mudstone in the Songliao Basin during artificial maturation. The hydrocarbons generated at 320–600 °C at two heating rates, 2 and 20 °C/h were quantified, and the maximum yields of C14+, C6-14 and C2-5 gaseous products corresponded to vitrinite reflectance (Ro) nodes of 1.18%, 1.76% and 2.5%, respectively. Chemical compositions of solid residues (pyrolysis products remaining after extraction by dichloromethane and methanol) with Easy%Ro values ranging from 0.49 to 2.5% were studied by elemental analysis and nuclear magnetic resonance. With increasing temperature, the solid residues presented sharp decreases in aliphatic fractions and significant increases in aromatic fractions, while a condensation reaction occurring in the residue was related to secondary coking and cracking reactions occurring after the peak oil window. Four structural models of the residues were investigated, demonstrating that three positive nonlinear stages occurred between fused aromatic carbon (XE BP) structures and hydrocarbon generation. At Easy%Ro < 0.89, the XE BP numbers were relatively stable, and the generated hydrocarbons mainly attributed to cleavage of heteroatomic functional groups (NSOs) of kerogen. During the peak hydrocarbon-generating stage (Easy%Ro values of 0.89–1.76), the XE BP numbers exhibited an obvious increase due to breaking of carbon chains and cyclization reactions, which was accompanied by formation of large quantities of C14+ oils and C6-14 hydrocarbons derived from direct cracking of kerogen. The XE BP numbers were growth slowing and highly cross-linked features at Easy%Ro values of 1.76–2.5% due to polycondensation, and a large amount of C2-5 gas generation was mainly attributed to oil cracking. A good coupling relationship between H/C atomic ratio and polycondensation of aromatic structures in evolution further strengthens research of molecular structure evolution in Type I kerogen. Moreover, comparison of the number of aromatic structures caused by alkyl bond breakage and condensation showed that the number of the former was higher than that of the latter before the peak of oil generation, whereas the number of the latter was obviously dominant after the peak of oil generation. Highlights: Molecular structure evolution of Qingshankou lacustrine Type I kerogen was characterized for the first time. Four Type I kerogen molecular models before C2-5 gases generation peak were constructed. Staged changes of fused aromatic carbon structures with maturity were observed. Aromatic structures caused by alkyl bond breakage and condensation were calculated and compared.